2021
DOI: 10.1108/ijesm-10-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis and mitigation for the city gas distribution projects

Abstract: Purpose This study aims to identify the operational and financial risks associated with the city gas distribution project in India and suggest appropriate strategies to mitigate them. Design/methodology/approach This study aims to identify the operational and financial risks associated with the city gas distribution project in India and suggest appropriate strategies to mitigate them. The survey data is evaluated using factor analysis to understand the latent structure of the critical risk factors. Second, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…This section discusses each risk and its potential implication for the CGD sector in India. Weighted average rank Sources Project cost escalation One (Kassem et al, 2019(Kassem et al, , 2020c(Kassem et al, , 2020a(Kassem et al, , 2020bHamzah et al, 2019;Kassem et al, 2019c); [Dey (2012), project risk management using multiple criteria decision-making technique and decision tree analysis: a case study of Indian oil refinery]; (Bin Seddeeq et al, 2019;Altyib and Alhakim, 2018) Improper project management Two (Kassem et al, 2019(Kassem et al, , 2020c(Kassem et al, , 2020a(Kassem et al, , 2020bHamzah et al, 2019;Kassem et al, 2019c;Rawat et al (2021a) risk analysis and mitigation for the CGD projects) Change in economic parameter (inflation, interest rate) Three (Khodeir and Mohamed, 2015;Van Thuyet et al, 2007;Kassem et al, 2019;Altyib and Alhakim, 2018;Kassem et al, 2020c;Hamzah et al, 2019;Mubin and Mubin, 2008;Kassem et al, 2019c;Mubin and Goryainov, 2007); [Dey (2012), project risk management using multiple criteria decision-making technique and decision tree analysis: a case study of Indian oil refinery]; (Van Thuyet et al, 2007;Rawat et al (2021a) risk analysis and mitigation for the CGD projects) Change in the currency exchange rate Four (Kassem et al, 2020a(Kassem et al, , 2020b(Kassem et al, , 2019(Kassem et al, , 2020cHamzah et al, 2019;Mubin and Mannan, 2013;Kassem et al, 2019c;Rawat et al (2021a) risk analysis and mitigation for the CGD pr...…”
Section: Implication For City Gas Distribution Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…This section discusses each risk and its potential implication for the CGD sector in India. Weighted average rank Sources Project cost escalation One (Kassem et al, 2019(Kassem et al, , 2020c(Kassem et al, , 2020a(Kassem et al, , 2020bHamzah et al, 2019;Kassem et al, 2019c); [Dey (2012), project risk management using multiple criteria decision-making technique and decision tree analysis: a case study of Indian oil refinery]; (Bin Seddeeq et al, 2019;Altyib and Alhakim, 2018) Improper project management Two (Kassem et al, 2019(Kassem et al, , 2020c(Kassem et al, , 2020a(Kassem et al, , 2020bHamzah et al, 2019;Kassem et al, 2019c;Rawat et al (2021a) risk analysis and mitigation for the CGD projects) Change in economic parameter (inflation, interest rate) Three (Khodeir and Mohamed, 2015;Van Thuyet et al, 2007;Kassem et al, 2019;Altyib and Alhakim, 2018;Kassem et al, 2020c;Hamzah et al, 2019;Mubin and Mubin, 2008;Kassem et al, 2019c;Mubin and Goryainov, 2007); [Dey (2012), project risk management using multiple criteria decision-making technique and decision tree analysis: a case study of Indian oil refinery]; (Van Thuyet et al, 2007;Rawat et al (2021a) risk analysis and mitigation for the CGD projects) Change in the currency exchange rate Four (Kassem et al, 2020a(Kassem et al, , 2020b(Kassem et al, , 2019(Kassem et al, , 2020cHamzah et al, 2019;Mubin and Mannan, 2013;Kassem et al, 2019c;Rawat et al (2021a) risk analysis and mitigation for the CGD pr...…”
Section: Implication For City Gas Distribution Industrymentioning
confidence: 99%
“…Moreover, developing a team of technicians to operate and maintain the CGD network is a challenge for long-term business (Gupta et al , 2017; Sircar et al , 2017). Rawat et al (2021a) identified 22 risks causing a delay in the commencement of the CGD projects and suggested 39 strategies to mitigate those risks. However, the research does not address all the risks causing a delay in CGD projects and recommends developing a comprehensive list of risk factors delaying the CGD projects.…”
Section: Introductionmentioning
confidence: 99%
“…Developing the natural gas business is a capital-intensive process and has a long payback period (Ishwaran et al , 2017; MoPNG, 2021). The other significant issues restricting natural gas growth are a lack of trained talent, absence of market-based pricing, price-sensitive consumers and taxation (Khan, 2018; Rawat et al , 2021; PIB, 2020). Zou et al (2018) have emphasized the aggressive development of domestic production, pipeline transportation capacity and LNG import and storage capabilities to expedite natural gas growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The major gas-consuming sectors in India are the fertilizer, power and city gas distribution businesses with 28%, 24% and 17% contributions, respectively. The country has introduced several reforms to boost the natural gas market growth, such as the implementation of a pricing mechanism, the introduction of the Hydrocarbon Exploration Licensing Policy (HELP), Open Acreage Licensing Policy (OALP) and city gas distribution licensing rounds (Abbasi, 2018; PPAC, 2021; Rawat et al , 2021). However, the results of these initiatives are not promising and encouraging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation